Sense of Calling and Job Crafting: A Test of Mediating and Moderating Effects - Ramadhanti, Shafira; Ekowati, Dian (Sekolah Tinggi Manajemen IPMI, 2024)
This research aims to explore the influence of the sense of calling on job crafting by looking at the mediating variables of occupational self-efficacy and career commitment, as well as the moderating effect of job autonomy. By involving 264 employees in Indonesia, this research used a quantitative approach with the convenience sampling method and PLS-SEM analysis techniques to test the formulated hypotheses. Of the nine hypotheses, this study supported seven hypotheses. This study found partial mediation in the mediating effect of occupational self-efficacy and career commitment. However, the moderating relationship in this research shows opposing results that job autonomy will weaken the relationship between career commitment and job crafting. Future research hopefully will be able to look further into the impact of job autonomy to provide a better explanation regarding the phenomena of job autonomy and job crafting, which, until now, various studies have still focused on the positive effects of both.